2013
DOI: 10.1136/bmjopen-2013-003823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of birth weight on the association between necrotising enterocolitis and red blood cell transfusions in ≤1500 g infants

Abstract: ContextReports evaluating a possible association between necrotising enterocolitis (NEC) and blood transfusion have been predominantly case–control studies. As the possible associations of disease with any variable on which cases and controls have been matched cannot be explored, a cohort study would offer a solution to this problem.ObjectiveOur objective was to evaluate the association between exposure to a packed red blood cell (PRBC) transfusion and development of NEC in a cohort where biases of matching ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…15,16 According to other works, it is generally accepted that premature neonates with TNEC have lower gestational ages, lower birth weights, and a late age of presentation (approximately 3 or 4 weeks after birth). 4,11,12,[17][18][19] The first statements were confirmed in the present research; on the contrary, the age at diagnosis was lower in the patients of this sample: 13 days in TR48. This investigation only included neonates who underwent surgical treatment for NEC: their age of presentation was similar to data published by Najaf (14 days at presentation of symptoms) and higher than the result given by Zhang (5.24 days at admission because of NEC) who performed studies which considered exclusive cases of NEC which received surgical therapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…15,16 According to other works, it is generally accepted that premature neonates with TNEC have lower gestational ages, lower birth weights, and a late age of presentation (approximately 3 or 4 weeks after birth). 4,11,12,[17][18][19] The first statements were confirmed in the present research; on the contrary, the age at diagnosis was lower in the patients of this sample: 13 days in TR48. This investigation only included neonates who underwent surgical treatment for NEC: their age of presentation was similar to data published by Najaf (14 days at presentation of symptoms) and higher than the result given by Zhang (5.24 days at admission because of NEC) who performed studies which considered exclusive cases of NEC which received surgical therapy.…”
Section: Discussionsupporting
confidence: 81%
“…Although Mally reported a series of six healthy, stable neonates developing a fulminant form of NEC after receiving a RBCT, most works indicate that patients with TNEC are usually in worse clinical conditions before the onset of NEC. 3,4,12,18 Thus, an accurate adjustment for clinical variables related to common comorbidities of low-birth-weight neonates is mandatory when investigations about TNEC show poorer outcomes in these patients. This adjustment was not performed in this work because there were no differences in major outcomes between the neonates classified as TNEC and those from group CN.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple retrospective cohort and case control studies have demonstrated an association between pRBC transfusion and subsequent development of NEC, 11-24 although 2 of these studies reported mixed results. 18,24 The risk of developing TA-NEC is reported to be 5-17 per 1000 transfusion events, accounting for 27%-38% of all NEC cases.…”
mentioning
confidence: 99%
“…18,24 The risk of developing TA-NEC is reported to be 5-17 per 1000 transfusion events, accounting for 27%-38% of all NEC cases. 11,12,14,15,18 These observational studies have led to the growing acceptance of TA-NEC as a valid clinical entity.…”
mentioning
confidence: 99%
“…Harsono i wsp. [11] wykazali protekcyjne działanie transfuzji uzupełniającej na wystąpie-nie NEC. W kolejnej pracy z 2013 r. autorzy ci wykazali, że transfuzja NUKKCZ zmniejsza ryzyko wystąpienia NEC, szczególnie w grupie najciężej chorych ELBW (analizowano m.in.…”
Section: Omówienieunclassified